Numerical Simulation of Effective Viscosity Distribution of Power-Law Engine Oil in Piston–Cylinder Lubrication Under High Shear Conditions - Andre Ronaldo Situmorang; Tulus (Talenta Publisher, 2026)
This study investigates the behavior of engine oil modeled as a non-Newtonian pseudoplastic fluid using the Power-Law equation under high operational conditions. The computational domain represents the lubricating oil film between the piston and cylinder wall. The governing equations include incompressible continuity and Navier–Stokes equa- tions coupled with a shear-rate-dependent viscosity model. Results show that shear rate con- centrates near the piston surface, reaching the order of 107 s−1 due to strong velocity gradients. As a consequence, effective viscosity decreases significantly in high shear regions, confirming shear-thinning behavior. The viscosity reduction directly affects the hydrodynamic pressure distribution while maintaining stable lubrication performance. These findings highlight the importance of incorporating shear-dependent viscosity to accurately predict lubrication characteristics in piston–cylinder systems operating at elevated shear conditions.